Effect of acclimation temperature on thermal tolerance between American lobster (Homarus americanus) collected in different lobster fishing areas in Atlantic Canada - Ryan A. Horricks; K. Fraser Clark; Kiersten L. Watson; Leah M. Lewis-McCrea; Gregor K. Reid (Canadian Science Publishing, 2024)
The American lobster fishery is the most economically significant commercial fishery in Atlantic Canada and takes place in waters that are warming due to climate change. Lobster are poikilotherms that tolerate a wide range of seasonal temperatures with an optimal range of 12-18 °C. Lobster in the Canadian Maritimes may be naturally acclimated to a wide range of temperatures and thus, could have a wide range of thermal tolerance that may be distinct across regions. The present study used non-invasive open-source tools to explore differences in thermal tolerance in real time between geographically separated lobster populations from around the Canadian Maritimes. Lobsters were acquired from six lobster fishing areas in the Canadian Maritimes and acclimated to either warm (15 °C) or cold (5 °C) water for two weeks before the onset of thermal trials. Geographic origin was not a significant predictor of estimated thermal maximum, while acclimation temperature was a significant predictor. These results suggest that thermal tolerance is more strongly linked to acclimation temperature than to geographic region.